UPAYA MEWUJUDKAN KELUARGA SAKINAH DALAM PERNIKAHAN PERJODOHAN ORANG TUA (STUDI KASUS DI DESA WADAK KIDUL KECAMATAN DUDUKSAMPEYAN KABUPATEN GRESIK) - Ahmad Fudloili; Ach. Faisol; Dzulfikar Rodafi (Jurnal Hikmatina, 2022)
A study entitled "Efforts to Realize Sakina's Family through Parental Arranged Marriage (Case Study in Wadak Kidul Village, Sat Duduk Sanpeyan, Gresic Regency)". Arranged marriages  in marriages  in the village of Wadak Kidul  follow Islamic procedures before the  marriage  is completed. It is advisable to choose a potential partner called Kafaa. Called "Kafaa," a balanced or harmonious couple with an equal, similar, or-matched marriage in the realization of the Sakina family achieves harmony between the couple and promotes the relationship between the family  and the environment. I have been married. Researchers use qualitative research, and this type of research uses case studies. Data collection was based on observational surveys, interviews, and documentation. When it comes to marriage, in the village of  Wadak Kidul, matchmaking is the will of the parents, but the decision depends on the children getting married. What husbands and wives do  to build Sakina's family through matchmaking marriage is mutual trust and respect, and always love for their children.Kata Kunci: Upaya, Keluarga Sakinah, Pernikahan Perjodohan